1994
DOI: 10.1063/1.112039
|View full text |Cite
|
Sign up to set email alerts
|

Auger electron spectroscopy study of the interaction of NO2 with Si(100)

Abstract: The nitridation of clean Si(100)-2×1 with NO2 has been studied using Auger electron spectroscopy (AES). In this letter we demonstrate that the interaction of Si(100) with NO2 leads to the efficient incorporation of nitrogen (N) and oxygen (O) in single crystal Si as opposed to the case of N2O on Si(100). A comparative study of the incorporation efficiency of N and O by the reaction of NO2 and N2O with Si(100) over a wide temperature range has been performed. It is observed that only a few Langmuirs (L) of NO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1996
1996
1997
1997

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Some workers detect significant amounts of N 2 O as a dissociation product. 41 Many reports show that NO must adsorb dissociatively at room temperature, 38,[45][46][47] but some observe only molecular species as the adsorbate. 48,49 The slope of this Stern-Volmer plot is 730 Torr -1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some workers detect significant amounts of N 2 O as a dissociation product. 41 Many reports show that NO must adsorb dissociatively at room temperature, 38,[45][46][47] but some observe only molecular species as the adsorbate. 48,49 The slope of this Stern-Volmer plot is 730 Torr -1 .…”
Section: Resultsmentioning
confidence: 99%
“…Some workers detect significant amounts of N 2 O as a dissociation product , but some observe only molecular species as the adsorbate. , Although there is agreement that dangling bonds are involved in adsorption, some researchers have found that the dangling bonds are capped by both N and O atoms, , while others find dangling bonds exclusively occupied by O. , …”
Section: Resultsmentioning
confidence: 99%
“…NO 2 is very corrosive compared to N 2 O, and by suitable choice of operating conditions, it might be possible to increase the atomic N concentration by delivering this molecule containing a very active nitrogen atom. Recently, an ultrahigh vacuum surface chemistry study showed that the nitridation of clean Si(100)-2×1 with NO 2 leads to the efficient incorporation of nitrogen (N) and oxygen (O) compared to N 2 O . While comparison with N 2 O at this ultrahigh vacuum dosing level does not connect directly to conditions of atmospheric oxidation and nitridation, the inference is clear.…”
Section: 2 Oxynitride Film Growthmentioning
confidence: 99%
“…
7 Summary of (a) N/Si for clean Si surface exposed to 10, 100, and 300 langmuir of NO 2 , (b) N/O for clean Si surface exposed to 500 langmuir of NO 2 , and (c) O/Si for clean Si surface exposed to 10, 100, and 300 langmuir of NO 2 at varying substrate temperatures. From ref .
…”
Section: 2 Oxynitride Film Growthmentioning
confidence: 99%
See 1 more Smart Citation